The role of mitochondria in osteogenic, adipogenic and chondrogenic differentiation of mesenchymal stem cells - Qianqian Li; Zewen Gao; Ye Chen; Min-Xin Guan (Protein & Cell, 2017)
Abstract Mesenchymal stem cells (MSCs) are progenitors of connective tissues, which have emerged as important tools for tissue engineering due to their differentiation potential along various cell types. In recent years, accumulating evidence has suggested that the regulation of mitochondria dynamics and function is essential for successful differentiation of MSCs. In this paper, we review and provide an integrated view on the role of mitochondria in MSC differentiation. The mitochondria are maintained at a relatively low activity level in MSCs, and upon induction, mtDNA copy number, protein levels of respiratory enzymes, the oxygen consumption rate, mRNA levels of mitochondrial biogenesis-associated genes, and intracellular ATP content are increased. The regulated level of mitochondrial ROS is found not only to influence differentiation but also to contribute to the direction determination of differentiation. Understanding the roles of mitochondrial dynamics during MSC differentiation will facilitate the optimization of differentiation protocols by adjusting biochemical properties, such as energy production or the redox status of stem cells, and ultimately, benefit the development of new pharmacologic strategies in regenerative medicine.